Correlation between blood and lymphatic microvascular density and cell proliferation in mouth floor and tongue squamous cell carcinoma - Bertini, Fernanda [UNESP]; do Prado, Renata Falchete [UNESP]; de Oliveira, Aline Júnia [UNESP]; Tera, Tábata de Melo [UNESP]; Rosa, Luiz Eduardo Blumer [UNESP]; Seabra, Julia Carvalho; Carvalho, Yasmin Rodarte [UNESP] (Elsevier, 2016)
Objective Despite the advances in medicine, the oral squamous cell carcinomas still have high incidence and are very important to study topics such as their lymphatic and microvessel density. This research assessed the correlation between histological grading, formation of new lymphatic and blood vessels and cell proliferation in squamous cell carcinomas (SCC). Methods Twenty-nine oral floor SCC and 30 tongue cases were assessed for their clinical characteristics and histological grading of malignancy. Results The presence of VEGF (vascular endothelial growth factor VG1), VEGF-C (vascular endothelial growth factor-C), CD105, to determine blood microvascular (MVD), and D2-40 to determine lymphatic density (LMD) was investigated using immunohistochemistry. Histological grading revealed that 73.3% of tongue and 96.67% of floor cases were classified as highly aggressive. Cell proliferation was greater on the floor; however, no significant difference was observed. Most carcinomas were VEGF negative (tongue 63.3% and floor 70.0%) and VEGF-C positive (tongue 73.3% and floor 79.3%). LMD was considerably greater on the tongue. High MVD values occurred in cases with greater cell proliferation. No relationship was determined between the growth factors VEGF and VEGF-C and MVD and LMD, respectively. Conclusion Floor of mouth SCC cases was morphologically more aggressive than tongue cases; however, in tongue carcinomas a greater quantity of lymphatic vessels could represent potential ways for locoregional cell dissemination of the neoplastic cells, independent of histological grading. Blood vascularization presented correlation with cell proliferation in intraoral squamous cell carcinoma and could be useful in the prognostic assessment of this neoplasm.
Keywords: CD105; D2-40; Ki-67; Oral cancer; Squamous cell cancer